A reflection on the role of women in Science, Dentistry and Brazilian Orthodontics - Cátia Cardoso Abdo QUINTÃO; Luísa Schubach da Costa BARRETO; Luciane Macedo de MENEZES (Dental Press Editora, 2021)
ABSTRACT Introduction: This paper reviews the history of women scientists in the 'Western world', whilst highlighting the persistent socio-structural issues that have led to the hiding and masking of the participation of women in Science. Further, a reflection is made of the situation of Dentistry, specifically in the field of Orthodontics in Brazil. The difference between genders is discussed, with the intention to map the progress of women in management and leadership positions, in both the academic and professional fields. Description: In Brazil, within Dentistry and Orthodontics, despite being in a numerical majority, women are still underrepresented in the area of professional leadership. This is true for Research Groups and Research Productivity; an example being the relatively low authorship of publications in a Brazilian journal of Orthodontics. They are also underrepresented as lead presenters at professional meetings, whilst there are also few female Presidents of professional organizations and associations. Conclusion: Despite being in a numerical majority, it is also important that women act in a more co-ordinated and consistent manner to achieve greater representation in these areas. The necessary changes in the structure in order to achieve this are not only of women and for women, but they must also involve the whole of society so that leadership, rights and duties are equally distributed between the genders.